1998
DOI: 10.1038/sj.bjp.0701888
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide‐evoked calcium signals and anion secretion in equine cultured epithelia that express apical P2Y2 receptors and pyrimidine nucleotide receptors

Abstract: 1 Experiments with a spontaneously transformed equine epithelial cell line showed that certain nucleotides increased intracellular free calcium ([Ca 2+ ] i ) in cells plated on glass coverslips. The rank order of potency was ATP=UTP45-Br-UTP, whilst UDP and ADP were ine ective. The response thus appears to be mediated by P2Y 2 receptors. 2 Nucleotides also increased short circuit current (I SC ) in cells grown into epithelial monolayers and the rank order of potency was UDP4UTP45-Br-UTP4ATP4ADP. The increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 21 publications
6
39
0
Order By: Relevance
“…Previous studies have identified the functional expression of apical purinoceptors (P2Y2) and pyrimidinoceoptors (P2Y4 and/or P2Y6) when the cells are grown on permeable supports. P2X receptors are not involved in mediating the nucleotide responses (16). This cell line also represents the simplest calcium-dependent secretory system in which cAMP-dependent Cl Ϫ secretion (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have identified the functional expression of apical purinoceptors (P2Y2) and pyrimidinoceoptors (P2Y4 and/or P2Y6) when the cells are grown on permeable supports. P2X receptors are not involved in mediating the nucleotide responses (16). This cell line also represents the simplest calcium-dependent secretory system in which cAMP-dependent Cl Ϫ secretion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…cystic fibrosis transmembrane conductance regulator function) is absent (15). Transepithelial secretion can only be activated by calciummobilizing agonists, such as extracellular ATP, UTP, UDP, and bradykinin (16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP-induced activation of KCa channels on a cell-attached configuration was seen as an increase in Popen, but this response only lasted for around 2·5 min. Similarly, ATP transiently increased the Ca¥-dependent Cl¦ secretion in monolayers of cultured equine sweat gland epithelial cells (Ko et al 1997;Wilson et al 1998). These results suggest that the ATP-induced increase in [Ca¥]é may serve as a common promoter for Cl¦ and K¤ channels in the process of transepithelial ion transport.…”
Section: Effect Of External Tea¤ and Iberiotoxinmentioning
confidence: 99%